Development of Quality Management in Kazakhstan (Quality Management and Effective Performance) Based on The Case Study of JSC “AZIA AVTO” - Mendekinov, Taur (2013)
Abstract Quality Management tends to be one of the challenging facets that are faced by companies in developing and newly-industrialised countries. As one of the developing country Kazakhstan experiences such difficulties. The focus of this dissertation is on assessing the effectiveness of Quality Management in Kazakhstan by identifying the compliance of the organisations with standards. The dissertation met its aims by studying extensively of the literature which is relevant and the practical research. The data for latter was conducted through Case Study of JSC “AziaAvto” by collecting and observing the relevant documentation as the core and using semi-structured interviews with Senior Management of the company. The study took into account some existing theories on quality management processes as in the case of TQM and Six Sigma not to mention other standards such as ISO 9000. Concluding, Kazakhstan had been reported of having its own developments on quality management and the researcher pointed out that such would help the country devise quality management processes that are relevant to their needs. The research debates on organisations in country to leverage their quality processes with economic prosperity organisations to leverage their quality processes with economic prosperity as well as implementing qualification requirements for quality managers.